Validation of a nutritional surveillance tape measure (Colombia Medica, 1990)
Anthropometric measurements were taken from a sample of 3772 Colombian children under 6 years of age for the purpose of validating an age-specific, 3-colored insertion tape for measuring arm circumference. Age in months, weight, nutritional classification with the insertion tape (green=wellnourished; yellow=at risk; red=malnourished), and arm circumference were recorded. The sample was classified according to weight for age with Fels Research Institute and National Center for Health Statistics references, according to: well nourished (> -1SD); at nutritional risk (>-2SD to < -1SD); malnourished (< -"SD). Cutoff points separating malnourished from not malnourished children (between green and yellow) were used for sensitivity specificity tests and for determining predictive values. Sensitivity varied from 98.4% to 88.9%, and specificity between 74.0% and 50.2%. The positive predictive value for children under six months old was low (27.9%), which is explained by the low prevalence of malnutrition in this age group in Colombia. Probabilities of error were established for all cutoff points. Based on the study's results, various cutoff points were adjusted, age groups under six months were discontinued, and scales for 24-35 and 36-47 months were developed. The design of the tape was also simplified to include all scales in one tape.